Depression, Anxiety, Stress, and Associated Factors among Pharmacy Students Following the COVID-19 Pandemic - Gulcan, Canan; Karaozan, Nurgül (My University, 2025)
COVID-19, which initially originated in the city of Wuhan, China at the end of 2019, caused millions of cases and deaths worldwide. Considering the conditions that arose during the pandemic, the psychological well-being of the students was affected by many factors related to COVID-19. This study has aimed to investigate the prevalence of depression, anxiety, and stress related to the COVID-19 and possible factors affecting depression, anxiety, and stress among pharmacy students. The mental health status of participants was examined using the Depression, Anxiety, and Stress Scale (DASS-21). Association analysis using non-parametric tests was performed for categorical, ordered, and dichotomous predictors. Logistic regression analysis was applied to investigate the effects of explanatory variables on the mental health of the students. Based on the findings, the prevalences of severe/extremely severe depression, anxiety, and stress were found to be 16.6%, 28.2%, and 12.0%, respectively. We also found significant effects of investigated factors, e.g., having a psychiatric disease, relationship with the family or friends, having anyone in the family who lost his/her job during the pandemic, having a need for psychiatric support, having anyone in the family diagnosed with COVID-19, on the depression, anxiety, and stress levels of the students. Our findings showed that the factors related to COVID-19 might have led to an increase in depression, anxiety, and stress levels among the students. These parameters must be taken into consideration both for the protection of students' psychological well-being and for the guidance of their education and training activities.
Keywords: COVID-19; mental health; pharmacy students